The Effect of Work Conflicts on Employee Performance - Soulthan Saladin Batubara (CERED Indonesia Institute, 2022)
This research aims to determine the Effect of Work Conflicts on Employee Performance at PT PLN (Persero) Binjai City. The data analysis techniques used are regression analysis, classical assumption test, t test, and coefficient of determination while tha data processed using SPSS (Statistical package for the Social Sciens) in version 16.0 for windows. The results of the study obtained showed that Work conflict has a positive and significant influence on the performance of the proven t value with a probability of sig 0.000, smaller than ? = 0.05. Furthermore, the coefficient of determination measured using R square is 0.221 (22.1%).